Characteristics Analysis of Small Insulated Vans Based on Thermoelectric Cooling - Yuan, Xiao-Hong; Qin, Chuang-Hui; Wang, Yi-Ping; Liu, Xun (Frontiers in Energy Research, 2021)
In cold chain logistics, refrigerated trucks are used for long-distance transportation across cities, and insulated trucks are used for short-distance delivery within cities. However, the small insulated vans for short-distance transportation like delivering home in urban have heat leakage and no pre-cooling, the transportation time of traffic congestion becomes longer, resulting in poor insulation effect. So, to achieve stable temperature control is difficult, it leads to a big fluctuation in the temperature of the cargo. The thermoelectric cooling technology has the unique advantages of compact structure, flexible layout, no refrigerant, and environmental friendliness, which is very suitable for controlling the temperature of the small insulated vans. In the paper, relationship among COP, working power, and working current of the designed thermoelectric cooler (TEC) is investigated first. And then the best working state of the TEC is obtained. Next, set hot and cold dual temperature zones to ensure the effective use of energy based on thermoelectric cooling characteristics, arranged the cooling device in the insulated van, and revealed the changes in the temperature of the compartment and the cargo through the actual vehicle test. Compared the thermal insulation effect of the compartment with or without thermoelectric cooling technology through CFD. According to the simulation results, the cargo temperature of the insulated van fluctuates between 4 and 6°C within 2.5 h of actual delivery in urban, the insulated van using thermoelectric cooling technology can make the temperature of the cargo fluctuate within 1.5°C. The above proved the good insulated effect of the thermoelectric cooling insulated vans. Finally, the influence of the working time of the thermoelectric refrigeration system on the temperature control effect is also studied. The research results have a certain guiding significance for the application of thermoelectric cooling technology in insulated vans.